1986
DOI: 10.1103/physreva.33.888
|View full text |Cite
|
Sign up to set email alerts
|

Angular and energy dependence of cross sections for ejection of electrons from water vapor. II. 15150-keV proton impact

Abstract: Absolute values of cross sections for electron ejection by protons of 15-150 keV energy have been measured as a function of the angle and energy of the electrons. The range of angles was 10" to 160" and the electron energy range was 1-300 eV. The doubly differential cross sections were also integrated over energy or angle to obtain singly differential and total cross sections and also average ejected electron energies. Good agreement is obtained with Senger's DDCS-MT (doubly differential cross section-mixed tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 18 publications
7
67
0
Order By: Relevance
“…Their atomic compositions and densities can be found in the ICRU Report 46 [31] and other sources, and a reasonable value of their mean binding energies can be estimated from the values of their molecular components, such as the water molecule, DNA bases and backbone, and amino acids [8,9,15]. We also show experimental data for water vapor [28,32,33], which nicely agree with our calculations above 100 keV, where the first Born approximation is applicable without further corrections. From our results, it seems that all the biological targets different from water have a larger ionization probability than water.…”
Section: Fig 2 (Color Online)mentioning
confidence: 82%
“…Their atomic compositions and densities can be found in the ICRU Report 46 [31] and other sources, and a reasonable value of their mean binding energies can be estimated from the values of their molecular components, such as the water molecule, DNA bases and backbone, and amino acids [8,9,15]. We also show experimental data for water vapor [28,32,33], which nicely agree with our calculations above 100 keV, where the first Born approximation is applicable without further corrections. From our results, it seems that all the biological targets different from water have a larger ionization probability than water.…”
Section: Fig 2 (Color Online)mentioning
confidence: 82%
“…These figures confirm the need to consider the target anisotropy, given the strong relationship between the symmetry of the initial and final MOs and the projectile trajectory. For example, for t 2 and t 3 the transition with the highest probability is from 3a 1 of H 2 O to 1s of H, and for t 4 it is from 1b 2 of H 2 O to 1s of H. This figure also shows the impact parameters at which the function bP (b) peaks (b = 4a 0 for t 2 and t 4 , b = 2.5a 0 for t 3 ) and the magnitude of the peaks (2.05a 0 for t 2 , 1.75a 0 for t 3 , and 1.25a 0 for t 4 ) for these three trajectories. In the picture for t 4 trajectory, we can observe the low, but non-negligible, contribution of SEC transitions into H(2l) energy levels to the total capture probabilities and, consequently, to the SEC cross sections.…”
Section: E Anisotropy and Orientation-averaged Cross Sectionsmentioning
confidence: 94%
“…Collisions between ions and molecules are relevant processes in cold plasmas, which have motivated a large amount of experimental [1][2][3][4][5][6][7] and theoretical [8][9][10][11][12] works.…”
Section: Introductionmentioning
confidence: 99%
“…We can at first mention the work of Dagnac et al [4] where total cross section measurements have been reported for SI and SC induced by protons with impact energies ranging from 2 to 60keV. Later on, Rudd et al [5] have published SI and SC total cross sections for 7-4000keV protons whereas Bolorizadeh and Rudd [6] reported doubly differential (differential in energy and angular transfers) and total SI cross sections for proton energies ranging from 15 to 150keV. More recently, Toburen [7] have reported total cross sections for electron capture by protons on water vapour.…”
Section: Introductionmentioning
confidence: 99%